Islamic Concept of Dignity of Labour and it’s Effect on the Nascent Entpreneurship Model - Badmus N. O. Abdul Azeez; Amidu Adinoyi Jimoh; Issah Zubairu Achara; Abubakar Yusuf Abdullahi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Islam as an important force that influences economic development and business performance and it is not impediment to business development, entrepreneurship and skill acquisition. Its economic system view of entrepreneurship is an integral part of wealth creation for Muslims. The objective of this paper is to see how the concept of Islamic dignity of labour could assist Muslim participants in the area of entrepreneurship. The methodology of this research is theoretical, hence; it applied qualitative approach. The data collection was conducted through personal views of experts in the area of Islamic worldview, Islamic entrepreneurship, ethics and understanding of al-Qur’an, Sunnah and other Islamic sources. There is no doubt that if the Islamic concept of dignity of labour is adhered to, it would assist the Muslims to identify the lawful and the unlawful aspects of participation in the area of entrepreneurship. Findings showed effect of the Islamic ethical model on the Islamic entrepreneurship design. It is therefore recommended that whatever role the Muslims want to play in the area of entrepreneurship, the ethics inherent in the Islamic concept of dignity of labour should be applied